Weathering geochemistry and Sr‐Nd fingerprints of equatorial upper Nile and Congo muds. (22nd March 2013) - Garzanti, Eduardo; Padoan, Marta; Setti, Massimo; Najman, Yani; Peruta, Luigi; Villa, Igor M.
Abstract: [1] This study investigates processes of sediment generation in equatorial central Africa. An original, complete and integrated mineralogical‐geochemical database on silt‐sized sediments derived from different parent rocks (basalt, granite, gneiss, metapsammite, sandstone) along the East African Rift from 5°S in Tanzania to 5°N in Sudan is presented and used to assess the incidence of diverse factors controlling sediment composition (source‐rock lithology, geomorphology, hydraulic sorting, grain size, recycling), with particular emphasis on chemical weathering. Key Points: Integrated mineralogical‐geochemical study of weathering in equatorial Africa Composition of river muds reflects weathering intensity and its controls Contrasting behavior of weathering indices quantifies recycling